Weight Gain and Health Affliction Among Former National Football League Players - Churchill, Timothy W. (Am J Med, 2018)
BACKGROUND: Professional American-style football players are among the largest athletes across contemporary sporting disciplines, and weight gain during the years of football participation is common. At present, the health implications of this early-life weight gain remain incompletely understood. We sought to define weight trajectories of former professional American-style football athletes and to establish their relationship with 5 health afflictions common in this population (cardiovascular disease, cardiometabolic disease, neurocognitive impairment, sleep apnea, and chronic pain). METHODS: A comprehensive health survey was distributed to former National Football League (NFL) players. Former players reported body weight at 4 key time points (high school, college, professional, and time of survey response) as well as maximal retirement weight. Logistic regression was used to assess associations between weight gain during and after football participation with health affliction. RESULTS: In this cohort of former NFL players (n=3,506, age 53±14 years), mean total weight increase from high school to time of survey response was 40±36 pounds, with the majority of weight gain occurring during and not after football participation. The prevalence of self-reported health afflictions ranged from 9% for cardiovascular disease to 28% for chronic pain. Weight gain during periods of active football participation (high school to college and college to professional) was independently associated with risk of multiple later life health afflictions in models adjusted for football exposure, post-career lifestyle variables, and post-career weight gain. CONCLUSIONS: Early-life weight gain among American-style football athletes is common and is associated with risk of adverse health profiles during later-life. These findings establish football-associated weight gain as a key predictor of post-career health and raise important questions about the central role of targeted weight gain in this population.